Social perceptions of carnivores across the globe – a literature review - Newsom, Amy; Lozano, Jorge; Martín-López, Berta (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2026)
To explore the factors underpinning human–carnivore relations, we reviewed 146 scientific publications recording associations of 34 socio-economic, actor-related, and species-related variables with people’s views on the beneficial and detrimental contributions of carnivorous terrestrial mammals to people. The associations with respective variables were coded as positive, negative, not significant, or mixed. They were then compared between geographic regions and carnivore families in a descriptive analysis and tested for significant differences among regions and carnivore families. The results indicate a pattern of associations that differs more strongly between regions than between carnivore families. This suggests that personal and societal aspects such as individuals’ personal beliefs and socio-economic situation have a stronger impact on their view of carnivores than animals’ biological characteristics. Consequently, we identify leverage point realms to improve human–carnivore relations, in particular re-connecting humans to nature and re-structuring institutions to improve carnivore management.
Keywords: Human-Wildlife Conflict; Human-Carnivore Interaction; Human-Wildlife Coexistence; Nature Contribution to People; Perception of Nature